Entrepreneurship among female immigrants. A case study in Madrid - Miguel Osorio-García-de-Oteyza; Ariana Pérez-Coutado; Mirian Jimenez-Sosa (Revista Iberoamericana de Estudios de Desarrollo, 2020)
The primary objective of this paper is to study and understand which factors determine the use or the non-use of ethnic resources in the business strategies of immigrant business women in Madrid. To achieve this goal, we studied the relationship between the structural factors of the host society, the resources that may be available to immigrant women in the context of their ethnic communities, and other individual characteristics. In this study, it is used a qualitative approach. We conducted 27 semi-structured interviews with immigrant entrepreneurs from Latin America (Brazil, the Dominican Republic, Ecuador, Venezuela, Bolivia, Paraguay, and Peru), Africa (Morocco and Senegal), and Eastern Europe (Bulgaria and Romania). The main conclusions reveal that the difference regarding the use of ethnic resources lies in the following factors: social networks, legal status, having access to ethnic resources, business location, and entrepreneur women’s origin.